Open Retropubic and Robot-Assisted Radical Prostatectomy in Prostate Carcinoma: Advantages of Methods - Nikolay Kolev; Jitian Atanasov; Vladislav Dunev; Boyan Stoykov; Rumen Kotsev; Alexander Vanov (Journal of Biomedical & Clinical Research, 2016)
Prostate cancer (PC) is the most common type of cancer in men inanumber of countries. The choice of surgical technique for radical prostatectomy (RP) concerns both patients and urologists. The choice is not easy to make, since data is still limited due to the lack of large multicentric randomized research trials. For three years (2011-2014), 244 patients with limited prostate cancer were operated in the Urology Clinic of the University Hospital in Pleven. Robot-assisted radical prostatectomy (RARP) was performed on 35 patients (14%), open retropubic radical prostatectomy (ORP) - on 199 patients (81%), and laparoscopic RP - on 12 patients (5%). The preoperative and post-op results from the first two groups were compared. For the follow-up period of 12 months, functional results in 82 patients of the ORPgroup were compared to the results in the 35 patients of the RARPgroup. The operative time was significantly longer in the RARPgroup, and blood loss was lower. The catheter stay was shorter in patients with RARP. The percentage of significant postoperative complications was 0%in the patients with RARPand 3%in the patients with an ORP. RARPpatients demonstrated better continence: 91%vs. 87%and erectile function46%vs.40%at 12 months.